The Fight Against Unregulated Fishing in the Arctic. Deterring Unregulated Fishing by Vessels under the 2018 Central Arctic Ocean Fisheries Agreement - Pancheva, Floriana (UiT Norges arktiske universitet, 2019)
Climate change and its consequences have an impact over the oceans and their marine ecosystems, especially in the Arctic. Following these changes, the ice-thickness is receding, and the Central Arctic Ocean waters are becoming more accessible. Some of the commercially valuable fish stocks are also observed to migrate northwards. Such migration might lead to growing fishing activities once vessels are able to be present at these waters. This would lead to increased possibilities for fishing in contradiction with established conservation and management measures. The Arctic states took initiative with regards to this issue and, in 2018, together with five more parties, signed a novel agreement, according to which no fishing shall be authorized until sufficient scientific knowledge is obtained. Therefore, the objective of this thesis is to investigate how the parties to this agreement can deter the unregulated fishing activities in the Central Arctic Ocean.